Enhancing corrosion resistance of Al-Cu/AZ31 composites synthesized by a laser cladding and FSP hybrid method. Issue 13 (3rd October 2019) - Liu, Fenjun; Ji, Yan; Sun, Zhiyong; Wang, Guozhang; Bai, Yanxia
ABSTRACT: High corrosion resistance Al-Cu powder-reinforced AZ31 Mg-based composites were produced by a laser cladding (LC) and FSP hybrid method. The microstructure characteristics, phase distribution, corrosion performance, and corrosion mechanism were ascertained using SEM, EDS, XRD and an electrochemical workstation. The composite coating of Al-Cu/AZ31 magnesium matrix composite mainly contains α-Mg solid solution, and β-Al12 Mg17, AlCu4 and Al2 CuMg intermetallic compounds. The intermetallic compounds did not change significantly with the proportion of Al and Cu powders. A large number of pores and microcracks in the composite coating prepared by LC were formed, whereas a sound bonding interface was observed between the LC Al-Cu coating and the matrix. In addition to the complete elimination of pores and microcracks, the microstructure of the LC composite coating became more refined, homogenized and densified due to dynamic recrystallization when it was subjected to FSP, especially FSP with pin. The sound bonding interface was not affected by FSP. The Al-Cu/AZ31 composite fabricated by LC and FSP hybrid method exhibited optimum corrosion performance. The maximum self-corrosion potential and self-corrosion current reached −0.907 V and 3.80 × 10 −5 A, respectively, and 58.0% and 24.5% of the matrix, respectively. The corrosion damage behavior was dominated by pitting corrosion.